2010
DOI: 10.3109/08880018.2010.496896
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma Presented with Polyhydramniosis

Abstract: Neuroblastoma is the most common extracranial solid tumor in pediatric age group. Clinical presentation of neuroblastoma is mostly related to origin of the tumor, extent of disease, and the presence of paraneoplastic syndromes. Here the authors report a neonate with neuroblastoma with an atypical presentation, diagnosed with postnatal abdominal ultrasonography performed due to polyhydramniosis in her mother during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…A chest X-ray showed plural effusion and a large mass in the right thoracic paravertebral region, and a diagnosis of neuroblastoma was confirmed with CT-guided fine-needle aspiration and the identification of urine metabolites. [ 3 ] Prior studies have reported prenatal findings such as the presence of fetal hydrops and polyhydramnios,[ 5 6 ] both of which were demonstrated in our case. Antenatal diagnosis by fetal MRI was reported by Blackman SC et al .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A chest X-ray showed plural effusion and a large mass in the right thoracic paravertebral region, and a diagnosis of neuroblastoma was confirmed with CT-guided fine-needle aspiration and the identification of urine metabolites. [ 3 ] Prior studies have reported prenatal findings such as the presence of fetal hydrops and polyhydramnios,[ 5 6 ] both of which were demonstrated in our case. Antenatal diagnosis by fetal MRI was reported by Blackman SC et al .…”
Section: Discussionsupporting
confidence: 68%
“…Aggressive high-stage disease tends to be found in patients who are diagnosed after the first year of life. [ 3 4 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Following abstract screening, 102 articles were determined to be outside the scope of the investigation and a further 14 full-text articles described cases of abdominal tumours without concomitant polyhydramnios. The remaining 27 publications describing 32 cases constituted the basis of this review ( Supplementary Table S1 ), [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%